(untitled) (Journal of Advanced Research in Social Sciences, 2023)
Countries implement corporate communication initiatives to improve their international relations, achieve business objectives, and strengthen their brands. Nation branding activities are mainly based on international events: sports, culture, and social issues. This paper evaluates the Dubai Expo 2020’s impact on the United Arab Emirates brand. We conducted a literature review about nation branding, and then we resorted to 15 indicators to analyze how the most important newspapers from some of the most influential countries (United States, Russia, France, and Germany) covered this event from a journalistic and corporate communication perspective. Our results proved that 82 articles were published about this topic; on the other hand, the most common criteria respected by these companies were quoting organizers (n=61), using the Expo’s logo (n=45), and the image of a falcon (n=43). We concluded that most media companies focused on facts related to the Expo 2020 and made references to the country’s identity (values, flag, falcon); however, most of them did not include links to the Dubai Expo and UAE public authorities’ websites.